The Influence Of Intercultural Communication On The Moral Consciousness Of Young People In The Era Of Globalization (Zien Journal of Social Sciences and Humanities, 2024)
In the era of globalization, intercultural communication has emerged as a pivotal factor influencing the moral consciousness of young people worldwide. As the interconnectedness of nations grows, cultural exchanges have become inevitable, shaping the values, beliefs, and ethical frameworks of the younger generation. This article explores the theoretical underpinnings of intercultural communication and examines its profound impact on youth's moral development. It also outlines the methodologies used to study this phenomenon and provides practical applications for educators and policymakers to harness intercultural communication effectively. The insights gathered aim to foster a deeper understanding of the role of intercultural exchanges in shaping the moral fabric of today's youth.